2021
DOI: 10.1111/hepr.13644
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of lenvatinib as third‐line treatment after regorafenib for unresectable hepatocellular carcinoma progression

Abstract: Aim Multiple molecular agents have been developed for treating unresectable hepatocellular carcinoma. This study aimed to elucidate the clinical efficacy of sequential treatment with lenvatinib after regorafenib failure. Methods From June 2017 to October 2020, 63 patients with Child–Pugh A and treated with regorafenib followed by sorafenib were enrolled (median age 71 years, 52 men, Barcelona Clinic Liver Cancer B:C = 23:40). They were divided into two groups, those treated with lenvatinib after regorafenib tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Our data suggest that ramucirumab treatment can expect consistent PFS in a wide range of patients. After the approval of atezolizumab and bevacizumab combination therapy, MTAs sequential therapy has become critical for HCC patients [ 19 , 20 , 21 , 22 , 23 ]. There are still clinical questions such as optimal sequential usage of available systemic treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that ramucirumab treatment can expect consistent PFS in a wide range of patients. After the approval of atezolizumab and bevacizumab combination therapy, MTAs sequential therapy has become critical for HCC patients [ 19 , 20 , 21 , 22 , 23 ]. There are still clinical questions such as optimal sequential usage of available systemic treatments.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has demonstrated that lenvatinib is a good option as a third-line therapy for those patients progressing under treatments with sorafenib and regorafenib. 71 Combinations of sorafenib with non-TKI molecular inhibitors, such as galunisertib (inhibitor of the transforming growth factor-β [TGF-β] receptor type I) (NCT01246986) 72 and refametinib (MEK inhibitor) (NCT01915589 and NCT01915602), the latter in patients with RAS -mutated HCC, 73 are also being explored.…”
Section: Targeted Therapies For Hccmentioning
confidence: 99%
“…Therapeutic decisions for late-line patients are mainly determined based on the tumor stage and the underlying liver dysfunction. Several single options evaluated the efficacy and safety of late line HCC compared to the best supportive care or placebo (12,21,22). For example, LEN prolonged OS, offering safety and tolerability in first-line treatment (5), as well as providing a good sequential treatment option after progression in the third line of unresectable HCC patients with better hepatic reserve function (21).…”
Section: Discussionmentioning
confidence: 99%
“…Several single options evaluated the efficacy and safety of late line HCC compared to the best supportive care or placebo ( 12 , 21 , 22 ). For example, LEN prolonged OS, offering safety and tolerability in first-line treatment ( 5 ), as well as providing a good sequential treatment option after progression in the third line of unresectable HCC patients with better hepatic reserve function ( 21 ). Furthermore, nivolumab was found to be safe in patients with Child-Pugh class B liver dysfunction ( 22 ).…”
Section: Discussionmentioning
confidence: 99%